THE ROLE OF LANGUAGE GAMES IN TEACHING ARABIC NON-NATIVE SPEAKERS - Obaid Mohammed Abdelhalim; Yusupova Dilorom (ARAB TILI GLOBALLASHUV DAVRIDA: INNOVATSION YONDASHUVLAR VA O‘QITISH METODIKASI MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2025)
This paper aims to verify the effectiveness of language games strategy in teaching language continuously [communicatively], by ensuring that this strategy can achieve the most important conditions and principles underlying the communicative approach to language teaching. In addition, through research in the educational literature, it was concluded that the strategy of language games is an effective strategy in teaching language continuously, thus; its use in the educational process brings many benefits and advantages that are difficult to achieve using other educational strategies.